The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/1365-2664.13591
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural land‐use history and restoration impact soil microbial biodiversity

Abstract: 1. Human land uses, such as agriculture, can leave long-lasting legacies as ecosystems recover. As a consequence, active restoration may be necessary to overcome landuse legacies; however, few studies have evaluated the joint effects of agricultural history and restoration on ecological communities. Those that have studied this joint effect have largely focused on plants and ignored other communities, such as soil microbes. 2. We conducted a large-scale experiment to understand how agricultural history and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 82 publications
3
48
0
1
Order By: Relevance
“…Agricultural practices may also have a long-lasting legacy in soil biota which can shape the composition and dynamics of these new forests (de la Peña et al, 2006;Turley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural practices may also have a long-lasting legacy in soil biota which can shape the composition and dynamics of these new forests (de la Peña et al, 2006;Turley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that microbial communities were not stochastically distributed on a wide scale and their biogeographical patterns were more influenced by soil type and land use (Ranjard et al, 2010). Recently, many anthropogenic activities were carried out to promote agricultural production and ecological restoration (Turley et al, 2019;Bonner et al, 2020;Tian et al, 2020). The Grain for Green program (GfG), a reforestation and ecological restoration program, changed local edaphic characteristics by shaping the structure of bacterial community (Ren et al, 2017;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, soil respiration, bacterial community structure, enzyme activities and physicochemical properties were different in wheat and apple planting systems (Wang et al, 2018). It is well demonstrated that land-use change, for example, the conversion of forests or grasslands to cultivated lands exert negative impacts on soil microbial diversity and multifunctionality (Berkelmann et al, 2020;Li, Delgado-Baquerizo, et al, 2019;Li, He, et al, 2019;Turley et al, 2020;Yang et al, 2021). However, the effects of the change of planting patterns on soil multifunctionality in the agroecosystems have been little explored.…”
mentioning
confidence: 99%